Work and academic performance in students of highandean alternative basic education - Arauco Acosta, Flor María (2020)
Objective. To describe the characteristics of work in the academic performance of students from Educational Center of Basic Education (CEBA) María Inmaculada. Methods. Basic type study, descriptive level and mixed techniques, research design: sequential explanatory (DEXPLIS). The sample comprised of 31 students that work from 14 to 18 years old. The statistical methodology used was descriptive and chi square tests were used. Results. It was found that the labor characteristics of the students are mostly very harsh, highlighting working hours greater than 8 hours a day, daytime subsistence jobs. Regarding academic performance, it was reported that 64% presented admissible grades of achievement, predicted according to the national learning scale (ECA) regulated by the Department of Education of Peru. It is adjusted to the literal, descriptive and categorical scales. The rest of the students are in a learning process, but none with academic deficiencies or failed grades. It was also determined that the legitimacy of the contract, the working days, the monthly salary, the payment period, the parental authorization to work and the autonomy of the work are not significantly related to academic performance (p> 0.05 ). Conclusion. Despite having very basic and defective working conditions with serious violations of labor policies, the results show that students have good academic performance. In addition, they showed an immutable self-improvement capacity that improves their training. However, it is important to protect their rights through norms and conditions that regulate adolescent work by local and national governments.